2008
DOI: 10.2353/ajpath.2008.070594
|View full text |Cite
|
Sign up to set email alerts
|

Development of Diabesity in Mice with Neuronal Deletion of Shp2 Tyrosine Phosphatase

Abstract: Obesity and diabetes, termed "diabesity," are serious health problems that are increasing in frequency. However, the molecular mechanisms and neuronal regulation of these metabolic disorders are not fully understood. We show here that Shp2, a widely expressed Src homology 2-containing Tyr phosphatase, plays a critical role in the adult brain to control food intake, energy balance, and metabolism. Mice with a neuron-specific, conditional Shp2 deletion were generated by crossing a pan-neuronal Cre-line (CRE3) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 39 publications
4
50
1
2
Order By: Relevance
“…9E). A number of studies have shown that mice lacking expression of SHP-2 either peripherally or centrally exhibit a variety of metabolic defects (64)(65)(66)(67). Altered mTORC1 signaling in these scenarios could contribute to these metabolic defects, given the important role of mTORC1/S6K1 in metabolism (1).…”
Section: Discussionmentioning
confidence: 99%
“…9E). A number of studies have shown that mice lacking expression of SHP-2 either peripherally or centrally exhibit a variety of metabolic defects (64)(65)(66)(67). Altered mTORC1 signaling in these scenarios could contribute to these metabolic defects, given the important role of mTORC1/S6K1 in metabolism (1).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the mammalian enzyme, stimulatory mutations of the human gene have been found responsible for several abnormalities, such as the pathological activity of Helicobacter pylori ( 54 ), Noonan syndrome ( 33 ), leukemogenesis ( 55 ), and human breast cancer ( 56,57 ). Although the relationship between SHP2 and hormonal imbalance has been analyzed, particularly in diabetes (58)(59)(60), the role of SHP2 in these disorders is not yet fully described or understood. Here we report a new physiological role of SHP2 in hormone action, particularly in the hormonal activation of steroidogenesis.…”
Section: Role Of Acsl4 In Shp2-mediated Effect On Camp-stimulated Stementioning
confidence: 99%
“…Potential causes include infectious agents, exposure to other environmental and dietary factors, hormonal and metabolic derangements, or a combination thereof. Animal models have provided a great deal of information about an association between metabolic diseases and LUT alterations (Azadzoi et al 1999, Kozlowski et al 2001, Krajewska et al 2008. Our laboratory has developed, over the last few years, an animal model of metabolic syndrome-associated hypogonadotropic hypogonadism by feeding adult male rabbits a high fat diet (HFD) for 12 weeks (Filippi et al 2009, Vignozzi et al 2011.…”
Section: Introductionmentioning
confidence: 99%